Marine biodiversity in Ha Long bay and Cat Ba archipelago - Thung, Do Cong; Ngai, Nguyen Dang; Thao, Dau Van; Sinh, Nguyen Van; Dong, Dao Minh (Vietnam Journal of Marine Science and Technology, 2019)
Ha Long bay - Cat Ba island located in the Northeast of Vietnam, in the area of Ha Long city (Quang Ninh province) and Cat Hai island district (Hai Phong city) is the largest limestone island in Vietnam. Features of biodiversity include the seven typical ecosystems of tropical limestone islands, namely tropical rainforest ecosystem, cave ecosystem, mangrove ecosystem, tidal ecosystem, coral reef ecosystem, soft-bottom ecosystem. Ha Long - Cat Ba also represents a high level of species diversity with 4,622 species of plants and animals on land and in the sea. In particular, on land there are 2,464 species, accounting for 53.3% and under the sea there are 2158 species, accounting for 46.7%. Up to 16 species and 114 species have been recorded in the Vietnam Red List and in the IUCN List, respectively. Together with hundreds of rare and precious species at national and regional levels, there are species of global conservation value, demonstrating that Ha Long bay - Cat Ba archipelago can possibly be a world heritage site according to the criteria of biodiversity (ix and x criteria).